University culture and sustainability: designing and implementing an enabling framework - Adams, Richard; Martin, Stephen; Boom, Katy (Elsevier, 2017)
Universities across the globe are giving increasing priority to the challenges of sustainability, encouraged by a variety of drivers including international and national policy, student and societal pressures. Many extant initiatives focus on a relatively narrow set of activities including: Technological solutions; Integrating sustainability across the curriculum; Integrating sustainability as an operational, strategic and outreach principle. These have met with mixed success, and have overlooked the importance of cultural change in embedding sustainability. Drawing and building upon previous studies in the cultural change and sustainability literature, the purpose of this article is to propose a conceptual framework for designing interventions and measuring and monitoring progress in building and embedding a university sustainability culture. Initial staff and student survey data from a UK university has been applied to the framework and their interpretation and implications are explored.
Keywords: University sustainability; Organizational culture; Environmental accountability; Wicked problem